A note on Tukey's polyefficiency - Yatracos, Yannis G. (My University, 1991)
The efficiency of an estimate Sn is usually computed at some underlying distribution. Because it is rare that a real situation can be represented by a single assumed model, Tukey proposed to compute instead the polyefficiency of Sn, that is the infimum of the efficiencies of Sn at a reasonable collection of distributions called corners. It is shown that high polyefficiency over a finite number of corners, seen as possible distributions of the n dimensional sample, implies at least as high an efficiency at any convex combination of these corners.
Keywords: Dimensional analysis; Efficiency; Robustness; Tukeys corners